Mapping research on Indonesian professional teacher: The bibliometric analysis - Setianingrum, Indah; Da Costa, Augusto (Journal of Professional Teacher Education, 2023)
This research aims to identify trends in scientific publications with the theme of Indonesian professional teachers. The research uses bibliometric analysis involving scientific publications from 1982 to 2023 in the Scopus database. The keyword we use is a professional teacher in Indonesia. The analysis results show that the trend of scientific publications with the keyword professional teacher in Indonesia has experienced a significant increase, with the peak occurring in 2020-2023. Indonesia is the country that has the highest contribution to scientific publications about Indonesian professional teacher . Wiyono, B.B. is a well-known researcher who has the most publications, while Lie, A. is a researcher who has the most total citations. Most scientific publications are in conference series, specifically in the Journal of Physics: Conference Series. The research results open up opportunities to conduct further research in areas that have not been widely researched, such as online learning communities, pedagogical content knowledge, professional development programs, professional knowledge, professional training, STEM (Science, Technology, Engineering, and Mathematics), teacher learning, and teaching practicum. The research results have implications for efforts to professionalize teachers in Indonesia.